2020
DOI: 10.22358/jafs/127689/2020
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Supplementing Lysophosphatidylcholine (LPC) in the Diet on Production Performance, Fat Digestibility, Blood Lipid Profile, and Gene Expression Related to Nutrients Transport in Small Intestine of Laying Hens

Abstract: This study was conducted to evaluate the effects of lysophosphatidylcholine (LPC) supplementation on egg production, fat digestibility, blood lipid profile and gene expression related to nutrients transport in brown egglaying hens. In total, 384 commercial laying hens were divided into 4 groups (8 replicates, 12 animals each): 1. positive control (PC), 2. negative control (reduced energy to 75 ME kcal/kg; NC), 3. NC-LPC 0.05%, and 4. NC-LPC 0.1%, accordingly to a completely randomized design. There were no sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In both terrestrial animals and aquatic animals, it has been found that the effects of LPC, although mainly acting as an emulsifier, were not restricted to lipid digestion and absorption [36,37]. In fish and shrimp such as turbot Scophthalmus maximus [8,38], rainbow trout [10,26], channel catfish [11], and tiger shrimp Penaeus monodon [39], LPC has also been used to overcome or mitigate the lipid metabolism disorders caused by high dietary lipid levels or fish oil replacement.…”
Section: Discussionmentioning
confidence: 99%
“…In both terrestrial animals and aquatic animals, it has been found that the effects of LPC, although mainly acting as an emulsifier, were not restricted to lipid digestion and absorption [36,37]. In fish and shrimp such as turbot Scophthalmus maximus [8,38], rainbow trout [10,26], channel catfish [11], and tiger shrimp Penaeus monodon [39], LPC has also been used to overcome or mitigate the lipid metabolism disorders caused by high dietary lipid levels or fish oil replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Khonyoung et al demonstrated that LPL supplementation could enhance lipid absorption via greater CD36 reaction [ 46 ]. Juntanapum et al reported that LPC supplementation could increase fat digestibility via upregulation of Niemann-Pick C1-like 1 (NPC1), one kind of sterol transporter [ 11 ]. Consistent with those results and current digestibility data, LPL increased the gene expression transporters of fatty acids (CD36 and FABP1).…”
Section: Discussionmentioning
confidence: 99%
“…Both CAT-1 and y+, LAT1 are the major system y+ transporter in most cells (system y+, with its ability to recognize cationic amino acids (lysine and arginine) [ 47 ]. The paper of Juntanapum et al revealed that the expression of CAT1 gene was elevated by LPC supplementation in lying hens’ feed [ 11 ]. In agreement with his results, we found LPL increased the expression of CAT1 and y+, LAT1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysophosphatidylcholine (LPC), a kind of bioactive lipid, has a robust antimicrobial and immunomodulatory potentials in broilers ( 1 5 ). The potent antimicrobial activity of LPC has been documented ( 1 3 ).…”
Section: Introductionmentioning
confidence: 99%